Peran Lembaga Simpan Pinjam Berbasis Masyarakat (LSPBM) Usaha Bersama Desa Siboang terhadap Pembangunan Ekonomi Pedesaan - Nirmala Dewi; Moh Arafa; Rika Suprapty (Universitas Negeri Surabaya, 2019)
The purpose of this research is investigatinhg and analyzing the basic needs of Community-Based Savings and Loan Institutions as well as efforts in local economic development and determining the strategies needed in developing the capacity of Community-Based Savings and Loan Institutions (LSPBM) and Small and Medium Enterprises (SME) in Siboang Village. This research also investiagates the role of LSPBM in the social and economic fields as well as internal and external factors to create strategies supporting the existence of LSPBM in Siboang village in order to empower local communities.This study applies a qualitative approach supported by the study of quantitative data. The data collected consists of primary data and secondary data. Primary data was collected by in-depth interviews with key figures and the researcher conducted observations, while secondary data were obtained from various literature studies including population documents from Sojol Subdistrict, Siboang Village and the 2016 Joint Venture LSPBM Annual Report. Information consisted of the Joint Venture LSPBM Management of Siboang Village, Secretary of Siboang Village, and Village Head. The technique of analyzing primary data and secondary data is processed through three stages of activity and carried out simultaneously, namely data reduction, data presentation and drawing conclusions through verification. Furthermore, qualitative data is processed into quantitative data, the researcher applies the SWOT analysis method that deals with internal and external factors of qualitative research that will produce a development strategy for the Joint Venture LSPBM.The results shows that the role of LSPBM is quite large in encouraging the local economy and is able to provide loans to LSPBM members in order to increase business, and it can develop and strengthen Joint Ventures LSPBM with SMEs in business and sharing cooperation for service and service coverage. It increases business capital with a savings pattern to get used to saving for members of the Joint Venture LSPBM. It also encourages LSPBM Assistance through institutions related in Donggala Regional Government for supervision and development of institutions, improvement of managerial human resources to be more optimal and professional.